2003
DOI: 10.1016/s0885-3924(02)00530-4
|View full text |Cite
|
Sign up to set email alerts
|

Pain Assessment in Elderly Patients with Severe Dementia

Abstract: The purpose of this study was to assess the reliability and validity of facial expressions as pain indicators in patients with severe dementia. Based on interviews with patients who could report pain, we defined characteristics of decubitus ulcers associated with reports of pain during dressing changes. We then evaluated 9 patients who had ulcers with these characteristics but were unable to communicate verbally because of severe dementia. We videotaped their facial expressions before and during their decubitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 11 publications
1
52
0
4
Order By: Relevance
“…Puntillo and colleagues (8) also noted a significant relationship between the number of behavioral indicators of pain and nurses' ratings of their postoperative patients' pain intensity. Thus, there is a growing body of evidence to support the frequently observed clinical observation that patients with pain respond behaviorally more often than patients without pain (38). An extension of this evidence is our documentation of the specificity of behavioral responses.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Puntillo and colleagues (8) also noted a significant relationship between the number of behavioral indicators of pain and nurses' ratings of their postoperative patients' pain intensity. Thus, there is a growing body of evidence to support the frequently observed clinical observation that patients with pain respond behaviorally more often than patients without pain (38). An extension of this evidence is our documentation of the specificity of behavioral responses.…”
Section: Discussionmentioning
confidence: 82%
“…These findings may cue clinicians into equating behavioral activity with degree of overall patient discomfort, especially in patients who are unable to self-report (38,43). These are the patients who are most at risk of experiencing unrelieved pain during a procedure because they cannot communicate verbally with their care providers.…”
Section: Discussionmentioning
confidence: 99%
“…48 The traditional signs of facial grimacing are accurate for the presence of pain but not its intensity. 49 Physician assessment of pain has been found to be accurate in mildly to moderately demented patients but less so in severely demented people. 50 Caregiver assessment of pain in one study had a 67% correlation with self-reported pain in patients with cognitive impairment (mean MMSE 15.7).…”
Section: Pain Assessmentmentioning
confidence: 99%
“…Keywords Elderly · Cognitive impairment · Pain assessment · Behavourial scale La douleur physique chronique est souvent sous-évaluée et n'est pas assez traitée [6] chez les personnes âgées présentant des difficultés à s'exprimer oralement [3,8,10]. L'importance des déficits sensoriels et cognitifs rend les outils d'autoévaluation inadaptés pour cette population.…”
Section: Mots Clés Personnes âGées · Déficit Intellectuel · éValuatiounclassified